Epigenetic code during mycobacterial infections: therapeutic implications for tuberculosis. (17th September 2021) - Fatima, Samreen; Kumari, Anjna; Agarwal, Meetu; Pahuja, Isha; Yadav, Vinod; Dwivedi, Ved Prakash; Bhaskar, Ashima
Abstract : Epigenetics involves changing the gene function without any change in the sequence of the genes. In the case of tuberculosis (TB) infections, the bacilli, Mycobacterium tuberculosis ( M.tb ), uses epigenetics as a tool to protect itself from the host immune system. TB is a deadly disease‐causing maximum death per year due to a single infectious agent. In the case of TB, there is an urgent need for novel host‐directed therapies which can effectively target the survival and long‐term persistence of the bacteria without developing drug resistance in the bacterial strains while also reducing the duration and toxicity associated with the mainstream anti‐TB drugs. Recent studies have suggested that TB infection has a significant effect on the host epigenome thereby manipulating the host immune response in the favor of the pathogen. M.tb alters the activation status of key genes involved in the immune response against TB to promote its survival and subvert the antibacterial strategies of the host. These changes are reversible and can be exploited to design very efficient host‐directed therapies to fight against TB. This review has been written with the purpose of discussing the role of epigenetic changes in TB pathogenesis and the therapeutic approaches involving epigenetics, which can be utilized for targeting the pathogen. Abstract : Epigenetic changes such as DNA methylation, histone, and RNA modifications regulate transcriptional profiles of immune‐related genes, which are targeted by Mycobacterium tuberculosis during infection for its long‐term survival in the host. Therefore, these epigenetic modifications are potentially attractive targets for the reversal of M.tb infection and reduction in disease pathogenesis by host‐directed therapy for the effective management of tuberculosis.